2021
DOI: 10.33736/ijbs.3159.2021
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Covid-19 Pandemic on Household Food Security: Experience from Sarawak, Malaysia

Abstract: This paper discusses how household food security is affected by the Covid-19 pandemic, using examples from Sarawak, Malaysia. Food security in Sarawak was affected by the implementation of the Movement Control Order (MCO) that was introduced to curb the spread of the Covid-19 disease. The MCO, and the subsequent phases that followed, imposed a varying degree of restrictions on movements in the country. This measure had serious repercussions on food security as it affects the distribution of food as well as how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…This is also reflected in figure 1. This is consistent with other research using high frequency (phone) survey data (Hirvonen et al, 2021; Tesfaye et al, 2020; Hirvonen, 2020) and appears to suggest that households have found ways of smoothing food consumption, either by finding alternative food sources, through philanthropic activity, government cash transfer or via other communal networks (Abdullah et al, 2021).…”
Section: Descriptive Statisticssupporting
confidence: 90%
See 1 more Smart Citation
“…This is also reflected in figure 1. This is consistent with other research using high frequency (phone) survey data (Hirvonen et al, 2021; Tesfaye et al, 2020; Hirvonen, 2020) and appears to suggest that households have found ways of smoothing food consumption, either by finding alternative food sources, through philanthropic activity, government cash transfer or via other communal networks (Abdullah et al, 2021).…”
Section: Descriptive Statisticssupporting
confidence: 90%
“…On the other hand several papers, especially those who have used high frequency (phone) survey data report the exact opposite: that covid-19 lockdowns have not caused a significant decrease in food security, but an actual improvement (Ibukun & Adebayo, 2021; Deaton & Deaton, 2020; Niles et al, 2020; Wolfson & Leung, 2020). The argument they make is that households are surprisingly resilient and have found ways to adapt either by finding alternative food sources, increased borrowing, through philanthropic activity or via other communal networks (Abdullah et al, 2021; Mahmud & Riley, 2020). This notwithstanding, there is likely to have been a reduction in the quality of food consumed, even though food availability was not seriously affected as households switch from vegetables and other rich foods, to less expensive processed carbohydrates (Ambikapathi et al, 2021; Prapkree et.al., 2021; Niles et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, he noted that the policies focused on the food production only, they did not address on the issue of distribution and the social relations of production (Henderson, 2022). Abdullah, Mersat and Wong (2021) conducted a study in Sarawak, Malaysia to understand how local people cope with food security issues during the lockdown phases. The study aimed to fulfill three research objectives: to investigate the conditions of the locals in terms of food security, how they coped to ensure they are food secure during the lockdown duration and the greatest challenges that they faced in maintaining their food supplies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, there are limited studies exploring food insecurity and coping strategies amongst undergraduate students during the COVID-19 pandemic in Malaysia. A previous study that explored food insecurity amongst the community in Sarawak, Malaysia found that they were food secure during the COVID-19 pandemic and implemented several coping strategies, such as finding alternative food sources and marketplace (20). Therefore, this study is aimed at exploring the food insecurity status and coping strategies adopted by undergraduate students.…”
Section: Introductionmentioning
confidence: 99%